GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Drought projections for the NW Iberian Peninsula under climate change - I. Alvarez; H. Pereira; M. N. Lorenzo; A. Picado; M. C. Sousa; J. J. Taboada; J. M. Dias (Climate Dynamics, 2024)
Drought can be considered an atmospheric condition, which rapidly goes beyond to affect multiple fields of the environment and human activities. The persistence of these atmospheric conditions can affect the recharge of surface and groundwater bodies due to a decrease in the volume of runoff and seepage, thus affecting human and environmental activities. In this context, the main aim of this work is to characterize the occurrence and variability of future droughts in Galicia over the twenty-first century. The methodology followed is based on the calculation and analysis of the Standardized Precipitation Index (SPI) in three-time scales (3, 6, and 12 months), using daily outputs of precipitation data from one RCM provided by the EURO-CORDEX project for different periods (reference from 1971 to 2005, and future from 2025 to 2060 and 2061 to 2096) and scenarios (RCP 4.5 and RCP 8.5). Using SPI-3, SPI-6, and SPI-12 projections, drought trends and potential changes in their characteristics were explored under RCP 4.5 and RCP 8.5 scenarios. In both scenarios, throughout the twenty-first century, a decreasing trend in SPI indicates an intensification of drought conditions over Galicia. Moreover, at the beginning of the century, under RCP 4.5, drought events will increase and will be slightly more intense but less persistent, while under RCP 8.5, the number of events will be almost the same, but shorter and less severe. Toward the end of the century, drought events are expected to be more numerous, less durable, and more intense under both scenarios.

Reinterpreting glacial deposits as a MTD ponding sediment gravity flows in the upper Mojón de Hierro Formation (Tepuel–Genoa Basin, Argentina) - Natalie B. McNall; John L. Isbell; Arturo C. Taboada; M. Alejandra Pagani; Eduardo Menozzo da Rosa (Sedimentary Geology, 2023)

Corrigendum to “Priorities to inform research on marine plastic pollution in Southeast Asia” [Sci. Total Environ. volume 841 (2022) Article 156704] - Lucy C.M. Omeyer; Emily M. Duncan; Kornrawee Aiemsomboon; Nicola Beaumont; Sujaree Bureekul; Bin Cao; Luis R. Carrasco; Suchana Chavanich; James R. Clark; Muhammad R. Cordova; Fay Couceiro; Simon M. Cragg; et al. (Science of The Total Environment, 2023)

Ceftazidime–avibactam treatment in bacteremia caused by OXA-48 carbapenemase-producing Klebsiella pneumoniae - O. Lima; A. Sousa; R. Longueira-Suárez; A. Filgueira; C. Taboada-Martínez; C. Portela-Pino; A. Nodar; F. Vasallo-Vidal; L. Martinez-Lamas; A. Pérez-Landeiro; M. Rubianes; MT. Pérez-Rodríguez (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Local versus Regional Soil Screening Levels to Identify Potentially Polluted Areas - C. Boente; S. Gerassis; M. T. D. Albuquerque; J. Taboada; J. R. Gallego (Mathematical Geosciences, 2020)

Aluminum fractionation in acidic soils and river sediments in the Upper Mero basin (Galicia, NW Spain) - L. Palleiro; C. Patinha; M. L. Rodríguez-Blanco; M. M. Taboada-Castro; M. T. Taboada-Castro (Environmental Geochemistry and Health, 2018)

Study of Water Quality in a Spanish River Based on Statistical Process Control and Functional Data Analysis - J. Sancho; C. Iglesias; J. Piñeiro; J. Martínez; J. J. Pastor; M. Araújo; J. Taboada (Mathematical Geosciences, 2016)

The problem of sampling on built heritage: a preliminary study of a new non-invasive method - N. Prieto-Taboada; C. Isca; I. Martínez-Arkarazo; A. Casoli; M. A. Olazabal; G. Arana; J. M. Madariaga (Environmental Science and Pollution Research, 2014)

Nutritional value of the marine algae wakame (Undaria pinnatifida) and nori (Porphyra purpurea) as food supplements - M. C. Taboada; R. Millán; M. I. Miguez (Journal of Applied Phycology, 2013)

Improved somatic embryogenesis of grapevine (Vitis vinifera) with focus on induction parameters and efficient plant regeneration - J. R. Vidal; J. Rama; L. Taboada; C. Martin; M. Ibañez; A. Segura; M. E. González-Benito (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Effects of sea urchin-based diets on serum lipid composition and on intestinal enzymes in rats - M. González; B. Caride; Ma A. Lamas; Ma C. Taboada (Journal of Physiology and Biochemistry, 2000)

Nutritional value of Holothuria forskali protein and effects on serum lipid profile in rats - E. Rodríguez; M. González; B. Caride; Ma A. Lamas; Ma C. Taboada (Journal of Physiology and Biochemistry, 2000)

Effects of orange and apple pectin on cholesterol concentration in serum, liver and faeces - M. González; C. Rivas; B. Caride; Ma A. Lamas; Ma C. Taboada (Journal of Physiology and Biochemistry, 1998)